Impact of agricultural inputs on the abundance of heavy metals (Cu, Zn) in soil, water, and plants in the south of Algeria - Guesmia, Hadjer; Tarai, Nacer; Ouamane, A. Tarek; Guimeur, Kamel; Masmoudi, Ali; Djellouli, Amir (Future Science, 2024)
he aim of our study is to assess the impact of agricultural inputs on the levels of heavy metals, specifically copper (Cu) and zinc (Zn), in soil, water, and plants in the oasis of El Ghrous, Branis, and Sidi Okba in Algeria. The existence of perilous substances in the surroundings is a significant ecological issue, endangering both human well-being and agricultural output. The overuse of fertilizers and pesticides may be causing heavy metals build-up. The aim will be to highlight a better understanding of the concentrations of copper (Cu) and zinc (Zn), considering as detrimental contaminants, after extensive utilization of agricultural inputs. In order to examine the levels of trace metals (TMs), we performed additional tests by comparing field samples using metal analysis techniques that involved ammonium acetate and EDTA, and detection by atomic absorption spectrophotometry. Our findings suggest that in soils affected by fertilizers and phytosanitary agents, the concentrations of Cu++ and Zn++ are below levels that would cause toxicity. Indeed, the levels of Cu++ are measured at 6.14 µg/g and the levels of Zn++ are measured at 4.97 µg/g. Nevertheless, the copper contents in irrigation waters from sites 01 and 02 beyond the levels that are considered dangerous. Similarly, copper levels in plants are categorized as hazardous. The findings emphasize the significance of implementing integrated pest management strategies in order to reduce the negative consequences of excessive use of agricultural inputs. Additionally, our study imposes the need to closely monitoring agricultural practices in order to mitigate environmental and public health hazards. Implementing sustainable farming practices and employing effective resource management strategies is crucial for safeguarding agricultural ecosystems and guaranteeing sustainable food production in the long run. Adopting an all-encompassing strategy is crucial for preserving the well-being of both the ecosystem and the populace.